Bacillus subtilis PB6 based probiotic supplementation plays a role in the recovery after the necrotic enteritis challenge - Aljumaah, Mashael R. (PLoS One, 2020)
In poultry production, birds are raised under intensive conditions, which can enable rapid spread of infections, with Clostridium perfringens-caused necrotic enteritis (NE) being one of the most devastating for the industry. The current investigation was conducted to evaluate the effectiveness of Bacillus subtilis PB6 probiotic supplementation on bird’s post NE recovery, based on chicken performance, cecal microbiota composition, ileum histomorphometric measurements, and short-chain fatty acid production in the cecum of the birds that were challenged with NE mid-production. Birds were split into four groups, including a negative control, positive control challenged with C. perfringens, group supplemented with B. subtilis probiotic, and NE challenged birds supplemented with B. subtilis probiotic. Following NE challenge birds were allowed to reach the end of production time at 40 days, and samples were collected to estimate if probiotic supplementation resulted in better post-NE recovery. Intestinal lesion score across the duodenum, jejunum, and ileum indicated that at the end of production timeline NE challenged birds supplemented with B. subtilis probiotic had lower intestinal lesion scores compared to NE challenged birds without probiotic supplementation implying improved recovery. Probiotic supplementation improved performance of NE challenged birds only in the post-NE recovery stage. NE challenged birds had a significant increase in cecal propionic acid, which was not observed in NE challenged birds supplemented with B.subtilus. Both B. subtilis supplemented groups (challenged and unchanged) were characterized by a significant rise in cecal acetic and butyric acid. Our results demonstrate that B. subtilis supplementation can assist the birds in dealing with NE outbreak and long term recovery.